Designing out crime in Western Australia: a case study - Cozens, Paul; Thorn, Michael (Emerald Group Publishing Limited, 2008)
Purpose of this paper: To present developments in designing out crime policy in Western Australia (WA) as a case study example, discussing the innovative Designing Out Crime Strategy, a systematic attempt at embedding such ideas within government policy.Design / methodologies / approach: Report on the systems approach adopted by the WA government, which draws together three key themes of designing out crime, namely; the design of the built environment, the ongoing management of the built environment and the use of product design to reduce opportunities for crime. The systems perspective is underpinned by an evidence-based approach across these three areas.Findings: Many existing international approaches to designing out crime are arguably limited, piecemeal and largely uncoordinated. This Strategy represents a comprehensive and holistic policy commitment to designing out crime. Research limitations / implications: The effectiveness of this Strategy is as yet unknown, but it arguably represents a comprehensive approach to embedding designing out crime within public policy frameworks. The future will ultimately judge the success or failure of this policy and key performance indicators are presented as part of the Strategy.Practical implications: It will be challenging to monitor the progress of this vision and whether adequate resources are made available to appropriate agencies to deliver the desired outcomes from the various actions identified within the Strategy. What is original / value of paper: No national or state jurisdiction has attempted to develop designing out crime policy in such a comprehensive manner and WA's Designing Out Crime Strategy arguably represents a truly proactive policy framework and a comprehensive vision and plan for action to reduce opportunities for crime in the design, planning, development and maintenance of the built form and in the design of products.